Zooplankton volume trends off Peru between 1964 and 2001 - Ayón P. (2004)
We thank several scientists from Instituto del Mar del Perú (IMARPE) for historical record information and Sonia Sánchez and Luis O. Duarte for discussions of an earlier version of this paper. Special thanks are extended to “Gordie” Swartzman (University of Washington) for his valuable comments and help in finishing this work during his visit to IMARPE. Monthly in situ SST data were contributed by the “Dirección de Hidrografia y Navegacion (DHN)” of the Peruvian Navy. Participation in the 3rd International Zooplankton Production Symposium, 20–23 May 2003, Gijón, Spain, was made possible with financial aid from Consejo Nacional de Ciencia y Tecnologı́a del Perú (CONCYTEC) and the Eastern Pacific Consortium for Research on Global Change in Coastal and Oceanic Systems (EPCOR). Finally, we recognize the very helpful comments of the two referees.